Kooperationen von Klein- und Mittelstädten mit ihrem Umland. Zur Umsetzung der österreichischen Stadtregionspolitik - Schorn, Martina; Priebs, Axel (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Theory and practice of city-regional policies are classically oriented towards metropolitan areas. The Austrian Conference on Spatial Planning (ÖROK) in cooperation with the Austrian Städtebund (Austrian Association of Cites), however, took on a pioneering role by involving small- and medium-sized cities in their urban region strategy as early as the early 2010s. In this context, numerous cooperative initiatives between smalland medium-sized towns and their surrounding areas have emerged in Austria over the past decade. Thereby, it gets obvious that these urban-regional cooperation are structured very differently in terms of content and institutional background. This paper is based on a comparative research in four case study areas that established urban-rural cooperation in Austrian small- and medium-sized towns with their surroundings, analysing different governance arrangements implemented in the four case study regions. The cases demonstrate how a discursive approach on the national level becomes a lived practice of equal, inter-municipal cooperation on a city-regional level.